2013
DOI: 10.1364/ol.38.004465
|View full text |Cite
|
Sign up to set email alerts
|

Generation of microwave radiation by nonlinear interaction of a high-power, high-repetition rate, 1064  nm laser in KTiOPO_4 crystals

Abstract: We report measurements of microwave (RF) generation in the centimeter band accomplished by irradiating a nonlinear KTiOPO4 crystal with a home-made, infrared laser at 1064 nm as a result of optical rectification. The laser delivers pulse trains of duration up to 1 μs. Each train consists of several high-intensity pulses at an adjustable repetition rate of approximately 4.6 GHz. The duration of the generated RF pulses is determined by that of the pulse trains. We have investigated both microwave- and second har… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…The 8-and 4-fold periodicity stems from the quartic terms inê. We note that the elements of the nonlinear secondorder susceptibility tensor for OR, d 0 ijk , and for SHG, d 2ωL ijk , could in principle be different but we have shown that in this experiment they actually are equal so that no superscript is needed to tag them [17]. Finally, as a consequence of the symmetry with respect to the interchange of indices j and k in (4), we will use the contracted indices form of the optical tensor that is represented by a 3 × 6 matrix of elements d il that operates on the E 2 column vector to yield the amplitude of the second-order nonlinear polarization [1].…”
Section: Theoretical Backgroundmentioning
confidence: 79%
“…The 8-and 4-fold periodicity stems from the quartic terms inê. We note that the elements of the nonlinear secondorder susceptibility tensor for OR, d 0 ijk , and for SHG, d 2ωL ijk , could in principle be different but we have shown that in this experiment they actually are equal so that no superscript is needed to tag them [17]. Finally, as a consequence of the symmetry with respect to the interchange of indices j and k in (4), we will use the contracted indices form of the optical tensor that is represented by a 3 × 6 matrix of elements d il that operates on the E 2 column vector to yield the amplitude of the second-order nonlinear polarization [1].…”
Section: Theoretical Backgroundmentioning
confidence: 79%
“…The laser beam to be characterized is allowed to impinge on the crystal by entering the receiver through an aperture whose diameter is equal or slightly larger than the laser beam waist. In contrast to the narrowbandwidth detection demonstrated in our previous work [12], the coaxial structure allows wide bandwidth detection of the generated radiation, as shown in Fig. 1 (bottom), where the measured transmission coefficient S12 is shown.…”
Section: Experimental Set-upmentioning
confidence: 82%
“…The OR phenomenon is present whether or not the crystal is properly oriented for efficient generation of second harmonic light (no phase matching requirement). To demonstrate that the observed phenomenon of microwave generation is a result of the nonlinear properties of the optical crystal, we have previously studied its dependence on the laser intensity and on the orientation of the laser polarization [12]. The phenomenon has been studied inside a microwave cavity, whose frequency of resonance coincides with the first harmonic of the train of laser pulses.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the microwave signal can be made independent of the laser beam polarization, provided the nonlinear crystal is properly cut. 9 In order to minimize the impact of the device on the laser beam that passes through it, the crystal is cut in such a way not to satisfy the phase matching condition for SHG. In this way the efficiency of SHG is reduced below 1%.…”
mentioning
confidence: 99%
“…No limitation in the device's response time is expected because of the electronic nature of the crystal response. 9 The voltage waveform output of the ultrafast PD is shown in Fig. 4(c).…”
mentioning
confidence: 99%